The year of living biblically : one man's humble quest to follow the Bible as literally as possible - Jacobs, A. J., 1968- (Simon & Schuster, 2007)
Raised in a secular family but increasingly interested in the relevance of faith in our modern world, A.J. Jacobs decides to dive in headfirst and attempt to obey the Bible as literally as possible for one full year. He vows to follow the Ten Commandments. To be fruitful and multiply. To love his neighbor. But also to obey the hundreds of less publicized rules: to avoid wearing clothes made of mixed fibers; to play a ten-string harp; to stone adulterers. The resulting spiritual journey is at once funny and profound, reverent and irreverent, personal and universal.